Passive hydrotherapy preserves cartilage and muscle integrity in a murine osteoarthritis model: potential role of integrin αV/TGF-β mechanotransduction - Di, Wu; Songyang, Wang; Ruibing, Feng; Yong, Huang; Hao, Hu; Xiaofeng, Duan; Yang, Rong; Yunxiang, Dong; Gang, Wu (Frontiers in Physiology, 2025)
BackgroundOsteoarthritis (OA) is a prevalent degenerative joint disease lacking curative treatments. While moderate physical activity such as swimming has been demonstrated to decelerate disease progression, its applicability is limited for individuals unable to perform high-impact or weight-bearing exercises. This study aimed to evaluate whether hydrotherapy—a low-impact, aquatic-based intervention—exerts joint-protective effects comparable to those of swimming in a murine model of OA.MethodsMale C57BL/6 mice were subjected to destabilization of the medial meniscus (DMM) surgery in the right knee to induce OA and were subsequently randomized into three groups (n = 16 per group): DMM group (control), Hydrotherapy, and Swimming. An additional sham-operated group (n = 16) was included for baseline comparisons. Mice in the intervention groups underwent respective exercise regimens (30 min/session, twice daily, 5 days/week) for 4 or 8 weeks. Histopathological analyses were performed to assess degenerative changes in subchondral bone, articular cartilage, and quadriceps muscle. Additionally, expression levels of key proteins involved in mechanotransduction and tissue remodeling were quantified.ResultsDMM surgery resulted in marked subchondral bone degeneration, cartilage matrix disruption, and quadriceps muscle atrophy. Neither hydrotherapy nor swimming attenuated subchondral bone degeneration. Both interventions mitigated muscle atrophy, potentially via modulation of integrin β1 signaling. Furthermore, hydrotherapy and swimming effectively preserved cartilage structure and suppressed extracellular matrix degradation. These chondroprotective effects are consistent with a reduction in peak joint loading during aquatic exposure and an associated attenuation of integrin αV and TGF-β/SMAD2/3 signaling, although causality was not directly tested in this study.ConclusionThese findings demonstrate that hydrotherapy confers cartilage-protective benefits comparable to swimming in a mouse model of OA. Possibly through the modulation of mechanosensitive signaling pathways, hydrotherapy may represent a viable, non-pharmacological strategy for delaying OA progression, particularly in individuals with limited capacity for conventional physical exercise.